Observation of Observation Results, Mathematics Learning Conducted at Tkq As-Suhriyah - Laila Zulfah Laila23 (Tajdid Al-Athfal, 2022)
ABSTRACT This observational study aims to determine the learning system carried out at TKQ As-Suhriyah. In studying mathematics, are children able to understand the mathematics lessons given by the teacher. Mathematics learning given at the early childhood level is still non-formal, where children have not been fully provided with actual mathematical material but are only introductory. . In mathematics education, for example in number recognition, numbers are first heard by mentioning the numbers one, two, three and so on. And show objects totaling one, two, three and so on, it doesn't mean the material immediately introduces the number symbol "two" because the child will be confused. With increasing intelligence and age, it is introduced to number symbols. Learning mathematics is a branch of subject that has a very broad scope and not only can count but also includes competencies that make the child understand and understand mathematical concepts. For mathematics education, it can be given to early age children with the learning by playing method or learning while playing, because when playing children will have the opportunity to explore, experiment and freely express themselves. By playing, children will accidentally understand certain mathematical concepts and see the relationship between one object and another. Keywords: Research, learning, mathematics AUD